PRIORITIZATION OF MITIGATION AND FLOOD RISK REDUCTION EFFORTS IN KOTA SINGKAWANG - Ranate, Chelsea; Soeryamassoeka, SB; Gunarto, Danang (Fakultas Teknik Universitas Tanjungpura, 2024)
Floods present significant challenges to urban areas globally, including Kota Singkawang in West Kalimantan, Indonesia, due to its susceptibility to seasonal monsoons. Mitigation efforts are crucial to protect lives, infrastructure, and sustainable development amidst urbanization and climate change. This research delves into flood risk reduction methods by integrating technical, economic, social, and environmental dimensions to aid policymakers and stakeholders in efficient resource allocation.This study aims to enhance flood resilience by identifying critical intervention areas through structured approaches, leveraging literature reviews, field surveys, and consultations with local authorities and communities. Prioritizing flood risk mitigation involves evaluating existing strategies and implementing structural measures like flood control buildings.The analysis findings indicate that the primary focus for mitigation efforts and flood risk reduction in Kota Singkawang should involve structural measures, specifically implementing flood control structures like polder systems and retention ponds to effectively address sea tides and heavy rainfall impacts. However, given the preliminary nature of this study, a more thorough investigation with comprehensive data is necessary to implement these structural technologies fully. This comprehensive analysis underscores the significance of comprehending flood risk complexities to formulate sustainable urban strategies in Kota Singkawang.